Muscle histopathology in children with spastic cerebral palsy receiving botulinum toxin type A. Issue 3 (5th January 2016) - Valentine, Jane; Stannage, Katherine; Fabian, Vicki; Ellis, Kevin; Reid, Siobhan; Pitcher, Christian; Elliott, Catherine
ABSTRACT: Introduction: Botulinum toxin A (BoNTA) is routine treatment for hypertonicity in children with cerebral palsy (CP). Methods: This single‐blind, prospective, cross‐sectional study of 10 participants (mean age 11 years 7 months) was done to determine the relationship between muscle histopathology and BoNTA in treated medial gastrocnemius muscle of children with CP. Open muscle biopsies were taken from medial gastrocnemius muscle and vastus lateralis (control) during orthopedic surgery. Results: Neurogenic atrophy in the medial gastrocnemius was seen in 6 participants between 4 months and 3 years post‐BoNTA. Type 1 fiber loss with type 2 fiber predominance was significantly related to the number of BoNTA injections ( r = 0.89, P < 0.001). Conclusions: The impact of these changes in muscle morphology on muscle function in CP is not clear. It is important to consider rotating muscle selection or injection sites within the muscle or allowing longer time between injections. Muscle Nerve 53: 407–414, 2016